Transgressing boundaries between film and music videos: Smarzowski, Kolski, and music videos in Poland. Issue 2 (4th May 2019) - Duda, Paulina
Abstract: While the investigation of how directors utilise popular music in their films has enjoyed relative popularity among Polish scholars, the way in which contemporary filmmakers transgress boundaries between 'film' and 'music video' in order to manifest their authorial strategies in other screen genres has not entered academic debates yet. The aim of this article is twofold. First, I will provide an overview of the marginalised position that the music video genre occupies in Polish-language academic discourse and suggest a few reasons for this negligence. Secondly, I focus here in particular on a comparison of the visual approaches and strategies prevalent in music videos directed by two notable contemporary Polish filmmakers: Jan Jakub Kolski and Wojciech Smarzowski. I will position their music videos in the context of their film production, arguing that their work for the music industry is an extension of their distinctive cinematic worlds and that it affects both the film language and the aesthetics of the music video genre ingeneral.